The Effect of Audio-Visual Media on Learning Outcomes in Arts, Culture, and Crafts Education: A Quasi-Experimental Study in Indonesian Elementary Schools - Sela Selfia; Yun Ratna Lagandesa; Muhammad Aqil; Zulnuraini Zulnuraini; Dyah Rahmawati; Surahman Wilade (Papanda Publisher, 2026)
Arts, Culture, and Crafts (SBdP) education in rural Indonesian elementary schools faces persistent challenges due to reliance on conventional lecture-based instruction, resulting in suboptimal student engagement and learning outcomes. Audio-visual media offers potential pedagogical advantages through dual-channel information processing, yet empirical evidence regarding its effectiveness in elementary arts education remains limited. This study investigated the effect of audio-visual media on second-grade students' learning outcomes in SBdP at Parigimpu'u Public Elementary School. A quasi-experimental design with nonequivalent control groups was employed, involving nine students divided into experimental (n=5) and control (n=4) groups. The experimental group received instruction incorporating audio-visual media demonstrating piggy bank construction techniques, while the control group received conventional instruction. Performance-based assessments measuring accuracy, neatness, creativity, and timeliness were administered as pretest and posttest. Data were analyzed using descriptive statistics and independent samples t-test. The experimental group achieved significantly higher posttest scores (M=95.83, SD=2.95) compared to the control group (M=85.94, SD=6.99), with statistical analysis confirming significance (t=2.975, p<0.05). All experimental group students surpassed the minimum passing threshold, demonstrating substantial improvement from baseline. Audio-visual media significantly enhances learning outcomes in elementary SBdP education by facilitating concrete visualization, reducing cognitive load, and promoting active engagement, supporting its integration into arts curricula particularly in resource-constrained rural schools.